MODELING INTERREGIONAL PATIENT MOBILITY: THEORY AND EVIDENCE FROM SPATIALLY EXPLICIT DATA - Michael Irlacher; Dieter Pennerstorfer; Anna-Theresa Renner; Florian Unger (International Economic Review, 2023)
This article provides theory and evidence on the spatial determinants of regional patient flows. We develop a theoretical model that explains a patient's choice to consult a general practitioner by a measure of spatial accessibility. We empirically test this gravity-type model using regional patient flows and detailed data on the spatial distribution of residents and physicians in Austria. Our measure of spatial accessibility is a crucial determinant of patient flows that substantially increases the explanatory power of regular gravity models. Counterfactual simulations show heterogeneous effects of exiting physicians on health-care accessibility and patient mobility.
Keywords: 330